The Effect of Gelatin on the Characteristics of Dioscorea Alata’s Starch Based Edible Film - Surhaini, Surhaini; Jatmiko, Wahyu Tri; Rinaldi, Rinaldi (Jurnal Bio-Geo Material Dan Energi, 2022)
ABSTRACT − Edible film is a thin layer made from material so that it functions as a barrier to mass transfer such as moisture, oxygen, lipids and dissolved substances. This study aimed to determine the effect of adding gelatin to edible films from starchh uwi and to determine the best concentration of the characteristics edible film. This study used a Completely Randomized Design (CRD) with 6 treatments tests were carried repeated 3 times so that 18 experimental units were obtained the addition gelatine of 0%, 1%, 1,5%, 2%, 2,5%, and 3%. The study showed the addition of gelatine concentration significantly affected transparancy, thickness and compressive strength but did not significant affect the water vapor transmission rate (WVTR) and solubility. The best treatment of gelatin concentration is 1% has a WVTR 154,24 ± 44,50 g/m2 24jam, transparancy of 8,98 ± 1,27 %/mm, solubility 24,41 ± 4,65 %, thickness of 0,17 ± 0,026 mm and compressive strength of 47,73 ± 3,50 N/m2.